Spectral pattern recognition of in situ FT-IR spectroscopic reaction data using minimization of entropy and spectral similarity (MESS): Application to the homogeneous rhodium catalyzed hydroformylation of isoprene - Chen, L. (2014)
10.1366/000370203321666489